Pemantau Lokasi Benda Bergerak Berbasis Web dengan Menggunakan Teknologi GPS Dan 3G - Lukas Tanutama; Daniel P. Hutabarat (ComTech: Computer, Mathematics and Engineering Applications, 2014)
This research aims to develop a system to monitor moving objects via web. The moving objects could be owned by individuals or company and can be used and managed independently. The system consists of three subsystems namely Mobile Geographical Location Sender (MGLS), Main Geographical Location Information Control (MGLIC), and Geographical Location Information User (GLIU). MGLS functions as geographical sensor. It retrieves GPS data and sends periodically to MGLIC as the main controller via 3G service. MGLIC is the receiving server and designed as web server as well. The web server is the host of a control application that processes GPS data that was sent by MGLS. The data is stored in a database and is centrally displayed. The processed information can also be used by GLIU, as another user that needs the information. Experimental test shows that the system can function according to the design.